Determination, implication, and satisfaction of shade selection in aesthetic dentistry - Asaad, Yasmin M.; Alsalem, Ali A.; Al Rabai, Nada A.; Alotaibi, Huda F.; Almuhaydib, Rayana N.; Alhaqabani, Tarfa S.; Alesawi, Laila M.; Alharbi, Khalid M.; Alkahtani, Dhuha A.; Alsulayyim, Abdulsalam A.; Alamoorat, Hamad M. (International Journal Of Community Medicine And Public Health, 2022)
Delivering an aesthetic solution that proportionally complements the patient's neighboring teeth is crucial. In the discipline of cosmetic dentistry, qualities like surface form, translucency, and color are the most important factors for creating esthetic prostheses. The final color of translucent ceramic restorations is determined by many factors such as the thickness of the porcelain veneer, the thickness and color of the luting agents and the color of the underlying tooth structure. In order to the results to be accurate, homogenous, and predictable—all of which are crucial for cosmetic dentistry—color matching must be carried out in a methodical manner. Lighting control at the site, the surrounding environment, state of the teeth, patient positioning, time, and clinician proximity to the tooth, squint test, visual color guidelines, Vita Classical shade guide, Vita Toothguide 3D-Master, Chromascop, customized shade guides, and dentinal and extended shade guides are all considered when mapping shade and translucency. A sensor, a signals conditioner, and technology that allows the conversion of the signals into data usable in the dental laboratory or operatory make up the three components of every color-measuring instrument. Colorimetry, spectrophotometry, digital photography, hybrid equipment, and spectroradiometry comprise a few types of color measurement technology. Both print and electronic shade systems need to be used when choosing the right shade in order to create acceptable aesthetics. The practitioner and patient are both satisfied when the appropriate shade is matched, and the patient also has a more appealing appearance.